DFT study of the electronic and optical properties of ternary chalcogenides AlX2Te4. (16th October 2019) - Azam, Sikander; Irfan, Muhammad; Abbas, Zeesham; Rani, Malika; Saleem, Tahira; Younus, Ayesha; Akhtar, Naseem; Liaqat, Bushra; Shabbir, Muhammad; Al-Sehemi, Abdullah G.
Abstract: Density functional theory (DFT) is applied first time on Ternary chalcogenides AlX2 Te4 (X = Zn, In) crystals by using first principles calculations. The electronic and optical properties were studied by ab-initio calculations via full potential linearized augmented plane wave method. It is established that both of compounds are direct band gap semiconductors and these band gaps are to be found at Γ-Γ symmetry points with 1.6 eV and 1.2 eV respectively. Here in we have explored the atomic/orbital origin of electronic states in the band structure for investigated materials from the density of states. From band structure and electronic properties indicate that valence and conduction band is mainly formed due to Zn–s, Zn–p, In–s, In–p, and Te–p orbitals and Zn–s, Zn–p, Al–s, Al–p, and Te-p orbitals respectively. The optical properties are computed from the spectra of dielectric function along with the other related optical properties like energy loss function, reflectivity, refractive index, extinction coefficient and conductivity for a continuous energy range of 0 to 14 eV. The study of the optical properties of this material demonstrates that these materials can be the effective candidates for the optoelectronic devices.